Validity and reliability of the Central Kurdish version of the Tinnitus Handicap Questionnaire (THQ-CK) - Mohammed Subhan Mohammed Hawramy; Sherko Saeed F. Zmnako; Muaid Ismaiel Aziz Baban (Russian Open Medical Journal)
Background — The goal of this study was to evaluate the reliability and validity of the Central Kurdish version of the Tinnitus Handicap Questionnaire (THQ-CK). Initially, the THQ was translated into the central Kurdish language, resulting in the THQ-CK. Subsequently, a supplementary assessment was conducted to ascertain the reliability and validity of the THQ-CK. Methods — The original version of the THQ was translated into the Kurdish language and then offered to 275 tinnitus patients. The procedures were performed using published guidelines for cross-cultural adaptation of health-related quality of life measures. The Tinnitus Handicap Questionnaire (THQ), the Tinnitus Primary Function Questionnaire (TPFQ), and the Visual Analogue Scale (VAS) for tinnitus loudness and annoyance were offered to participants suffering from tinnitus. In addition, a pure-tone audiogram was obtained. Results — Our study encompassed a total of 275 patients (132 female, 143 male). Their mean age was 47.43±14.32 years. Of them, 43.6% previously worked in a noisy environment. The internal consistency of the THQ total score and its factors (Cronbach’s alpha of total scores: 0.833; factors: 0.949, 0.959, 0.960) suggested excellent reliability. The test-retest correlation coefficient demonstrated excellent reliability (0.9) for the total scores, and factors 1 and 2, but moderate reliability (0.66) for factor 3. The THQ-CK demonstrated good construct validity, as indicated by the strong correlation (r=0.757) between the THQ-CK and TPFQ scores. Conclusion — The evaluation of the validity and reliability of the THQ-CK suggests that it is a reliable instrument for assessing the impact of tinnitus on individuals in the central Kurdish-speaking population. The study contributes valuable information to the field of tinnitus research and opens up avenues for future cross-cultural studies.